APPLICATION OF ARTIFICIAL INTELLIGENCE IN ISLAMIC EDUCATIONAL INSTITUTIONS USING THE LEARNING ORGANIZATION APPROACH: A CASE STUDY OF DARUNNAJAH INSTITUTE AND UNIVERSITY IN INDONESIA - Novrizal, Nesa; Manaf, Sofwan; Masad, Masruin; Samiyono, Samiyono (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
This study investigates the integration of Artificial Intelligence (AI) in Islamic educational institutions, specifically focusing on Darunnajah Institute and University in Indonesia, utilizing the Learning Organization (LO) approach. The study aims to explore how AI can enhance the educational process while maintaining the core spiritual and moral values of Islamic education. A qualitative research methodology was employed, which included stages of identification, screening, eligibility, and inclusion, to select studies that examine AI’s potential in personalized learning, religious practices, and ethical challenges within Islamic education.The findings highlight AI’s capacity to improve academic performance, streamline administrative processes, and support personalized learning paths. However, the study emphasizes the importance of balancing technological advancements with the preservation of Islamic values. AI tools, such as real-time feedback for Quranic recitation, show promising outcomes in cognitive development but cannot replace human educators' roles in fostering moral and spiritual growth. Ethical concerns, including data privacy, algorithmic bias, and transparency, are critical to ensuring AI's alignment with Islamic principles.The study proposes a hybrid model of AI integration that combines technology with traditional teaching methods. Future research should focus on developing ethical frameworks for AI, especially regarding privacy and algorithmic fairness, and explore further how AI can enhance both academic and character development in Islamic education. This research contributes to the literature on AI in Islamic education and provides practical insights for institutions aiming to adopt AI while preserving their religious and ethical foundations.